An Analysis of the Paradoxical Role of Religion in the Occurrence of Peace and Conflict in Human Society - Akpuh, Charles C.; Mavalla, Ayuba Gimba (NIU Journal of Social Sciences, 2021)
For many years, scholars have battled with understanding and explaining the connection between religion, peace, and conflict.  However, the plethora of the ensuing thoughts and explanations has rather created more confusion than resolution of the matter, especially because scholars have hardly agreed on any of the numerously evolving perspectives.  With the aim of discovering a way out of the observed dilemma, this paper embarked on an analytical approach, incorporating the propositions of the indivisibility thesis to highlight and examine the basic characteristics of religion and how they influence peace and conflict between and among people.  It was discovered that the major factors that determine whether religion will promote peace or conflict in the society at any instance are the indivisibility of the associated tenets and its proneness to selfish manipulation; that the inherent characteristics of religion make it equally inclined to peace and conflict as well as to manipulation which affects its influence on them.  The paper concluded that despite the equal inclination of religion to peace and conflict, it is more prone to conflict than peace, especially because of its inherent proneness to segregation and manipulation.  The paper, therefore, recommended a general re-orientation of all stakeholders of peace and conflict in relation to the role of religion in the society, following the realist, rather than the utopian, claims that help maintain the unwanted influence of religion on the balance of peace and conflict in human society.  This re-orientation is necessary because it will help clear the scholarly confusions on ground and to place religion in its rightful place in the promotion of the necessary balance of peace and conflict in human society. Keywords: Conflict, Human Society, Indivisibility, Peace, Religion